(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this study, we introduce the concepts of N-ideals of types (, ) and (, ), along with soft N_-sets, soft N_-sets, and soft N_-sets. Additionally, we define soft N-subalgebras and N-ideals within the context of Sheffer stroke Hilbert algebras and explore various properties of these structures. The paper also provides characterizations of N-subalgebras of types (, ) and (, ), as well as N-ideals for both of these types. Furthermore, we further examine their corresponding soft versions, extending the algebraic framework in the setting of Sheffer stroke Hilbert algebras.